Философско-культурологическое измерение системы "человек-культура" в условиях техноинтеллектуализации антропосферы: терминологический анализ - Карпенко, Виталий Евгеньевич (НТУ "ХПИ", 2016)
В статье эксплицируется потенциал терминологического анализа философии техноинтеллектуализации культуры для разрешения проблемы концептуализации философско-культурологического измерения феномена действительных и возможных процессов техноинтеллектуализации антропосферы. Сформулировано фундаментальное понятие для данной сферы исследований – «техноинтеллектуализация культуры». Это требующая гуманизирующего осмысления совокупность процессов как формального, так и содержательного прямого и опосредованного преобразования средствами техноинтеллекта в глобальных масштабах конституирующих культуру программ человеческой жизнедеятельности, преобразования всех сфер культуры.

The potential of the philosophy of culture technointellectualization terminological analysis for solution of the problem of the conceptualization of real and possible anthroposphere technointellectualization processes phenomenon philosophic-culturological dimension is explained in the article. A fundamental concept for this sphere of investigation is formulated – "the technointellectualization of culture". It is the requiring humanizing set of processes of both formal and substantial, direct and indirect global conversion of culture constituting programs of human life, the transformation of all spheres of culture by technointelligence means. Also in this context there are formulated the concepts of the technointellectualization of anthroposphere, the society being technointellectualized.
Philosophic-culturological aspect of the "man-culture" system in conditions of anthroposphere technointellectualization: terminological analysis
Keywords: интеллект искусственный; философия; техноинтеллект; artificial intelligence; technointelligence